Protective Effects of Gemigliptin, a Dipeptidyl Peptidase-4 Inhibitor, against Cisplatin-Induced Nephrotoxicity in Mice - Choi, Seung Hee; Leem, Jaechan; Lee, In-Kyu (Mediators of Inflammation, 2017)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are widely used antihyperglycemic agents for the treatment of type 2 diabetes mellitus. Recently, the pleiotropic actions of DPP-4 inhibitors have drawn much attention. In the present study, we aimed to examine whether gemigliptin, a recently developed DPP-4 inhibitor, could protect against cisplatin-induced nephrotoxicity. We showed that pretreatment with gemigliptin attenuated cisplatin-induced renal dysfunction, as shown by analysis of plasma creatinine levels and blood urea nitrogen and histological damage. Elevated plasma levels of active glucagon-like peptide-1 were observed in gemigliptin-pretreated mice after cisplatin treatment, compared to that in cisplatin alone-treated mice. Gemigliptin attenuated cisplatin-induced apoptotic cell death, as assessed by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling and Western blot analysis in the kidneys. Gemigliptin also decreased the plasma levels of tumor necrosis factor-α and monocyte chemoattractant protein-1 and attenuated nuclear staining of nuclear factor kappa-B p65 in the kidneys. In addition, gemigliptin increased the protein expression of heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO1) in the kidneys of cisplatin-treated mice. Taken together, these results suggest that pretreatment with gemigliptin protects against cisplatin-induced nephrotoxicity in mice, possibly via inhibition of apoptotic cell death and inflammatory responses through induction of HO-1 and NQO1 expression.